SIRT3 (Sirtuin-3) Prevents Ang II (Angiotensin II)–Induced Macrophage Metabolic Switch Improving Perivascular Adipose Tissue Function - Wei, Tong; Gao, Jing; Huang, Chenglin; Song, Bei; Sun, Mengwei; Shen, Weili (Arteriosclerosis, thrombosis, and vascular biology, 2021)
Infiltrated macrophages actively promote perivascular adipose tissue remodeling and represent a dominant population in the perivascular adipose tissue microenvironment of hypertensive mice. However, the role of macrophages in initiating metabolic inflammation remains uncertain. SIRT3 (sirtuin-3), a NAD-dependent deacetylase, is sensitive to metabolic status and mediates adaptation responses. In this study, we investigated the role of SIRT3-mediated metabolic shift in regulating NLRP3 (Nod-like receptor family pyrin domain-containing 3) inflammasome activation. Approach and Results: Here, we report that Ang II (angiotensin II) accelerates perivascular adipose tissue inflammation and fibrosis, accompanied by NLRP3 inflammasome activation and IL (interleukin)-1β secretion in myeloid SIRT3 knockout (SIRT3 ) mice. This effect is associated with adipose tissue mitochondrial dysfunction. In vitro studies indicate that the deletion of SIRT3 in bone marrow-derived macrophages induces IL-1β production by shifting the metabolic phenotype from oxidative phosphorylation to glycolysis. Mechanistically, SIRT3 deacetylates and activates PDHA1 (pyruvate dehydrogenase E1 alpha) at lysine 83, and the loss of SIRT3 leads to PDH activity decrease and lactate accumulation. Knocking down LDHA (lactate dehydrogenase A) or using carnosine, a buffer against lactic acid, attenuates IL-1β secretion. Furthermore, the blockade of IL-1β from macrophages into brown adipocytes restores thermogenic markers and mitochondrial oxygen consumption. Moreover, NLRP3 knockout (NLRP3 ) mice exhibited reduced IL-1β production while rescuing the mitochondrial function of brown adipocytes and alleviating perivascular adipose tissue fibrosis. SIRT3 represents a potential therapeutic target to attenuate NLRP3-related inflammation. Pharmacological targeting of glycolytic metabolism may represent an effective therapeutic approach.